Teacher Professional Development - Zulfitri Zulfitri (JADEs Journal of Academia in English Education, 2020)
Professionalism of teachers is often attributed to three factors are quite important, namely the competence of teachers, teacher certification and teacher professional allowance. The third factor is the background that was allegedly closely associated with the quality of education. Professional teachers as evidenced by its competence shall promote the establishment process and product performance which can support the quality of education. Competent teachers can be evidenced by the acquisition of teacher certification following an adequate allowance according to the size of Indonesia. Today, there are a number of teachers who have been certified, it will be certified, has gained professional allowance, and will acquire the professional allowance. The fact that the teachers have been certified is a strong assumption, that the teacher already has competence. The problem that arises then, that the teacher is assumed to have had the competence which is only based on the assumption that they have been certified; it seems in the long term it is difficult to be accountable academically. Evidence have been certified, the teacher is present condition, which is generally a quality teacher resources shortly after certification. Therefore, the certification is closely related to the learning process, the certification cannot be assumed to reflect the competence of a superior lifetime. Post- certification should be an early milestone for teachers to constantly improve competence by means of long-life learning. To facilitate the improvement of teacher competence, it is necessary that a competence is initiated in order to manage the development of teachers’ professionalism.